Um lugar (in)existente: o "país" de Mossoró" nas tramas da consciência histórica - Carvalho, Sadraque Micael Alves de (2012)
This work aims to analyze, on the one hand, how the academy has created the spatial term the country of Mossoró and, on the other hand, is to discover, by the teachers testimony, how the History teaching works with this spatiality. The academic production in Mossoró-RN, particularly during the last two decades of the century XX, focuses on the practices that built a historic memory based on political interests of the Rosado family. Therefore, this work is divided in three chapters. In the first one, we identify how the academic production has created a group of meanings related to the country of Mossoró , because it is a way to realize how this place is seeing and understand. In the second one, there is an explanation about the ideology concepts, that structure meanings created by the academic production, as well as the historic conscience that is used to think about the dynamic of teaching History. In the third, we analyze how teachers, expressing their historic conscience, figure meaning to this country of Mossoró